NiCo₂O₄@NiO hybrid arrays with improved electrochemical performance for pseudocapacitors - Liu, Xijun; Liu, Junfeng; Sun, Xiaoming, 1955- (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Hybrid metal oxide architectures have attracted much attention in recent years due to their great potential to meet the ever-increasing requirements of high energy density and power density in energy storage applications. Here, we report a facile hydrothermal synthesis of a binder-free hierarchical NiCo₂O₄@NiO nanowire array (HNW) with robust adhesion, for use in electrochemical capacitors (ECs). The resulting hybrid array electrode exhibits superior pseudocapacitive performance with high specific capacitance (2220 F g⁻¹), remarkable rate capability, and excellent cycling performance (93.1% retention after 3000 cycles). Furthermore, a NiCo₂O₄@NiO//AC asymmetric supercapacitor was prepared and found to exhibit a high energy density (31.5 W h kg⁻¹) at a power density of 215.2 W kg⁻¹ and superior cycling stability (89% of the initial capacity retention at 50 A g⁻¹ over 3000 cycles). This outstanding electrochemical performance benefits from the synergistic contribution of the composite and unique hierarchical architecture. Such highly integrated hybrid array electrodes will be extremely helpful towards the fabrication of high-performance nanoenergy systems.